2014
DOI: 10.1007/s00024-014-0981-x
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Surface Geostrophic Circulation Climatology and Annual Variations Inferred from Satellite Altimetry and GOCE Gravity Data

Abstract: We have studied, for the first time, variations in absolute surface geostrophic currents (SGC) using satellite data only. The proposed approach combines 18 years' altimetry data, which provide reliable measurements of absolute sea level (ASL), with a gravity field and steady-state ocean circulation explorer geoid model to obtain dynamic topography, and achieves unprecedented precision and accuracy. Our proposal overcomes the main limitations of existing approaches based solely on altimetry data (which suffer f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…where W β = 1 and W s = 0 at the equator, while W β → 1 and W s → 0 as the latitude increases (at 5 • N and 5 • S). This formula has been described in more detail in previous studies [18,19]. Suzuki et al [20] compared several sources of wind speed datasets and found that the Cross-Calibrated Multi-Platforms (CCMP) dataset was the most accurate.…”
Section: Methodsmentioning
confidence: 99%
“…where W β = 1 and W s = 0 at the equator, while W β → 1 and W s → 0 as the latitude increases (at 5 • N and 5 • S). This formula has been described in more detail in previous studies [18,19]. Suzuki et al [20] compared several sources of wind speed datasets and found that the Cross-Calibrated Multi-Platforms (CCMP) dataset was the most accurate.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Tenze et al (2014) calculated the thickness of the Earth's crust in North-Eastern Pakistan, while Braintenberg (2015) identified tectonic structures with GOCE data in Africa and across-continents. Furthermore, the gradients from the gravimetric satellite mission can be combined with other data, e.g., altimetric to study the changes occurring not only in the solid Earth structures, but also in glaciers (Rummel et al 2011a), atmosphere (Garcia et al 2016;Liu et al 2016) and ocean circulations (Sanchez-Reales et al 2016).…”
Section: Introductionmentioning
confidence: 99%